Copper isotopes as a means of determining regional metallurgical practices in European prehistory: A reply to Jansen. (May 2018) - Powell, W.; Mathur, R.; Bankoff, A.H.; John, J.; Chvojka, O.; Tisucká, M.; Bulatović, A.; Filipović, V.
Abstract: We present a detailed response to the critique by Mr. Jansen of the paper " Digging Deeper: Insights into Metallurgical Transitions in European Prehistory through Copper Isotopes ". When we consider Cu isotope ratios of European Eneolithic and Early Bronze Age artifacts in the context of their local geological settings, climates, and archaeological contexts, Mr. Jansen's hypothesis that 63 Cu enrichment results from the adoption of fahlore ores is untenable. In both Serbia and Central Europe, the earliest copper production is associated with 65 Cu-enriched ores and subsequently produced artifacts yield lower ranges δ 65 Cu. This shift in Cu isotopic composition correlates with the initial use of predominantly hypogene ores, not with variations in their trace element content. Essentially the expanded dataset supports the conclusions that were presented in the original paper—Cu isotopes are an effective means of delineating the transition from oxide-based smelting to methodologically more complex smelting of sulphide ores in prehistoric Europe with its relatively limited production and trade. Mixing did not mask the critical Cu isotope signatures in this setting. Therefore, Cu isotope compositions of artifacts can be used to interpret the mineralogical character of the ores from which they were produced, regardless of their provenance, as long as trade networks remained within a region of similar climatic history. Graphical abstract: Highlights: Cu isotopes are effective for differentiating ore types (oxide versus sulphide) used for production of artifacts. Predominantly sulphide ores were employed in the Early Bronze Age in Serbia and the Middle Bronze Age in Central Europe. Differences in ore use with time are due to mining duration, long-term climatic conditions, and pyrotechnological changes, and introduction f pyrotechnology.